Memahami Pengasuhan Digital: Faktor Pendukung, dan Tantangan bagi Orang Tua - Ulfa Masfufah; Naila Naswa Salsabila (Universitas Negeri Malang, 2024)
The use of digital technology, especially smartphones, continues to increase from year to year, from children to teenagers and adults. The use of digital technology for children must be accompanied by parents. Parental assistance in this case is called digital parenting. This article aims to provide an overview of digital parenting for children and adolescents through the integration of empirical findings from previous articles. The second objective is to find factors that play a role in parental digital parenting. The method used is a narrative literature review. The data used in this research were seven articles from 17 articles that were collected. The results show that digital parenting is influenced by various factors, namely: parental self-efficacy, technology access, internet access, demographic factors, socio-economic conditions and parenting style. The existence of programs such as eParenting also plays a role in digital parenting. Most parents understand both the risks and benefits of digital technology, and there are efforts by parents to reduce these negative impacts. AbstrakPenggunaan teknologi digital khususnya smartphone terus meningkat dari tahun ke tahun, dari mulai anak-anak hingga remaja dan juga dewasa. Penggunaan teknologi digital bagi anak haruslah dengan pendampingan orang tua. Pendampingan orang tua dalam hal ini disebut pengasuhan digital. Artikel ini bertujuan untuk memberikan gambaran pengasuhan digital pada anak-anak dan remaja melalui integrasi temuan empiris dari artikel terdahulu. Tujuan kedua yaitu mencari faktor yang berperan dalam pengasuhan digital orangtua. Metode yang digunakan adalah narrative literature review. Data yang digunakan dalam penelitian ini adalah tujuh artikel dari 17 artikel yang berhasil dihimpun. Hasilnya menunjukkan bahwa pengasuhan digital orang tua dipengaruhi oleh berbagai faktor yaitu: efikasi diri orang tua, akses teknologi, akses internet, faktor demografis, kondisi sosial ekonomi dan gaya pengasuhan. Adanya program seperti eParenting juga berperan dalam pengasuhan digital. Sebagian besar orang tua telah memahami baik resiko maupun manfaat teknologi digital, dan ada upaya-upaya dari orang tua untuk mengurangi dampak negatif tersebut.